The Law-Making Function of the UN Committee on the Rights of Persons with Disabilities - Uerpmann-Wittzack, Robert (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Evolution through subsequent practice is particularly marked in international human rights law, where international human rights bodies produce abundant practice. Here, the question arises as to whether the practice of these bodies alone suffices to determine the content of international human rights obligations or whether organ practice must be backed up by state practice or forms of implicit state consent. This question shall be analysed with regard to the UN Convention on the Rights of Persons with Disabilities (CRPD) of 13 December 2006 and the Committee on the Rights of Persons with Disabilities established under 34 CRPD. Although the Convention is only ten years old, its Committee has already produced quite an important corpus of practice, and it has shown its willingness to construe the Convention in a rigorous way which makes important parts of current domestic state practice with regard to persons with disabilities illegal.
Keywords: Komitet Praw Osób Niepełnosprawnych ONZ; Konwencja o Prawach Osób Niepełnosprawnych; obowiązki w zakresie praw człowieka; źródła prawa; stanowienie prawa